Reading jesus eaudiobook A writer's encounter with the gospels. - Gordon, Mary (Tantor Media, 2009)
In the introduction to this remarkable book, Mary Gordon is riding in a taxi as the driver listens to a religious broadcast, and she reflects that, though a lifelong Christian, she is at odds with many others who identify themselves as Christians. In an effort to understand whether or not she had "invented a Jesus to fulfill my own wishes," she determined to read the Gospels as literature and to study Jesus as a character. What results is a vibrantly fresh and personal journey through the Gospels, as Gordon plumbs the mysteries surrounding one of history's most central figures. In this impassioned and eye-opening book, Gordon takes us through all the fundamental stories—the Prodigal Son, the Temptation in the Desert, the parable of Lazarus, the Agony in the Garden—pondering the intense strangeness of a deity in human form, the unresolved more ambiguities, the problem posed to her as an enlightened reader by the miracle of the Resurrection. What she rediscovers—and reinterprets with her signature candor, intelligence, and straightforwardness—is a rich store of overlapping, sometimes conflicting teachings that feel both familiar and tantalizingly elusive. It is this unsolvable conundrum that rests at the heart of Reading Jesus .